Molecular Dynamics Simulation on Creep Mechanism of Nanocrystalline Cu-Ni Alloy - Kasum Kasum; Fajar Mulyana; Mohamad Zaenudin; Adhes Gamayel; M. N. Mohammed (Jurnal Fisika FLUX, 2021)
Creep mechanism is an essential mechanism for material when subjected to a high temperature and high pressure. It shows material ability during an extreme application to maintain its structure and properties, especially high pressure and temperature. This test is already done experimentally in many materials such as metallic alloys, various stainless steel, and composites. However, understanding the creep mechanism at the atomic level is challenging due to the instruments  limitation. Still, the improvement of mechanical properties is expected can be done in such a group. In this work, the creep mechanism of the nanocrystalline Cu-Ni alloy is demonstrated in terms of molecular dynamics simulation. The result shows a significant impact on both temperature and pressure. The deformation supports the mechanisms as a result of the grain boundary diffusion. Quantitative analysis shows a more substantial difference in creep-rate at a higher temperature and pressure parameters. This study has successfully demonstrated the mechanism of creep at the atomic scale and may be used for improving the mechanical properties of the material.